National Congress and electoral system - Fernández Baeza, Mario (Revista de Derecho Público, 2015)
The following pages represent a stubborn attempt to place the debate in the academic and practical seat it deserves. It is about specifying the conceptual and methodological bases of the electoral systems, linking them with the Chilean reality of its binominal system, arriving at suggestions for the necessary constitutional and legislative decisions that allow or provide a framework for its necessary reform.